Analysis Of Translation Techniques On Justin Baldonismovie Five Feet Apart - Anggraini, Siti (Universitas Muhammadiyah Sumatera Utara, 2021)
This objectives of this study are to classify the types of translation techniques from Movie Five Feet Apart and how the translator applied those techniques into target language. This research is descriptive qualitative method.Researchers chose Movie Five Feet Apart because this movie was liked by many teenagers and made researchers want to analyze it. This movie is taken from the true story of a novel, where the two teenagers like each other but are blocked fivefeet because of cystic fibrosis. In data collection, the researcher analyzed by watching the film repeatedly to get an understanding of this movie, in order to getthe information needed in form of the application of those techniques into target language.The data which was found analyzed with the following steps:managedata, select movies, read scripts and watch movies, analyze Five Feet Apartmovies. The results of this study indicate that first, based on my analysis theresearcher found 464 dialogues of Movie Five Feet apart that contains 12 types of translation technique.The percentage of each translation technique was found as follows: (1).Adaptation occurred 4 (0.59%), (2). Amplification occurred 15 (3.31%), (3).Borrowing occurred 132 (19.7%), (4). Calque occurs 3 (0.45%), (5). Discursive Creation occurred 4 (0.59%), (6). Established Equivalent occurred 93 (13.86%),(7). Generalization occurred 6 (1.32%), (8). Linguistic Compression occurs 3(0.45%), (9). Literal Translation occurred 119 (17.73%), (10). Particularization occurred 15 (3.31%), (11). Reduction occurred 35 (7.52%), (12). Transposition occurred 34 (5.22%).